Kelayakan Usaha Ayam Broiler (Studi pada Usaha Peternakan di Desa Cibinong) - Elpawati Elpawati; Achmad Tjachja Nugraha; Ratu Shofiatina (Caraka Tani: Journal of Sustainable Agriculture, 2018)
Indonesia poultry consumption has increased year by year, with the average positive growth rate of 4.6%. This situation can be a chance for both small and large scales of poultry farmers, considering that poultry consumption is increasing every year. The rate of poultry production in Gunung Sindur was correlated with the amount of the existing poultry farms. Romli Farm was a small scale poultry farm in Gunung Sindur, Bogor. This poultry farm, with no partnership, could independently survive amongst the many other existing farms. However, although the opportunities were wide open, this business was not always viable for the farmers because many of small-scale farmers could not be able either to increase the income or to carry on the business. This research aimed to study the income, financial feasibility (NPV, IRR, Net B/C Ratio, and PP), the BEP of Selling Price, and the BEP of Product in Romli Farm.